Revision of the African genus Neomacrocoris (Hemiptera: Heteroptera: Nepomorpha: Naucoridae) - Sites, Robert W.; Mbogho, Aaron Y. (Zootaxa, 2012)
The genus Neomacrocoris is endemic to Africa and represented by 12 known species with scant mention in the literature. Presented here is an annotated list of the species summarizing the literature and providing available diagnostic information, illustrations, known repositories of types, and a taxonomic key. Also presented here are descriptions of four new species of Neomacrocoris from South Africa, Tanzania, and Uganda. Macrocoris transvaalensis Distant is transferred to Neomacrocoris. N. handlirschi var. armatus Poisson 1948 is synonymized with N. handlirschi handlirschi (Montandon 1909). Further, designated here are a neotype for N. usambaricus Montandon and lectotypes for N. dubius Poisson, N. handlirschi (Montandon), N. hungerfordi Poisson, N. nanus Poisson, N. parviceps (Montandon), and N. transvaalensis.